Konsep Universalitas Islam dan Katolik serta Realitas Dinamikanya dalam Kehidupan Manusia - Martinus H.W. Adiyanto; Imanuel Bonaventura F.L.; Andreas Fajar Purwanto (Parahyangan Catholic University, 2022)
Human life is closely related to a pluralistic reality. Pluralism is a world reality that cannot be avoided and rejected. Pluralism itself needs to be considered a gift God gives humans. A pluralistic world provides more color to human life. This requires an attitude of inclusiveness in social life so that humans can avoid harmful conflicts. The attitude of inclusiveness can be found in the universalistic spirit of the two major religions. Catholic Christianity and Islam adhere to universalism in spreading their religious teachings. Almost in every part of the world, we can find adherents of Christianity, Catholicism, and Islam. Universalism in both religious teachings requires everyone to be able to join as a member regardless of ethnic and national background. Inclusiveness in the spirit of the universalism of the two religions is often tarnished by the actions of fundamentalist extremist individuals or groups. The particular group's activities certainly cannot generalize the whole teaching in the religion. However, it can be a warning that the echo of exclusivity needs to be echoed again.